Lojas francas do Brasil: um estudo sobre o processo de regulamentação e implementação - (:unkn) unknown (Universidade Federal do Pampa, 2020)
The present study aims to describe the process of regulation and implementation of free stores in Brazil. We opted methodologically for a descriptive character research exploratory, since it was a new theme, constantly changing during the elaboration of the work. Using the case study as a method, we sought to investigate for different data sources the unfolding of the situation. This work makes a temporal cut between 2009, when the law of stores was approved until 2019, when the first stores were effectively implemented. The main results were the definition of the differences between the free shops in Brazil and the free shops Uruguayans both with regard to the requirements prior to opening. And also, with regard to operation. Under the Brazilian regime, it is permitted to sell to consumers in the country, while Uruguayans cannot buy in duty-free shops in their country. Uruguayan standardization works with a detailed positive list, while in Brazil there is a small negative list of two items with a broad and interpretable description. In Uruguay there is no limit for the value of sales, even though there is an exemption quota for Brazilian tourists to bring to Brazil products purchased in Uruguay. It is concluded that the duty-free stores in Brazil are justified by the development they provided in Uruguay, however, there are still challenges to be overcome, such as achieving security adaptations of what was idealized to the operators' daily reality and that everything be done respecting the norms so that the border cities can have the growth expected economic impact with the installation of Brazilian free shops.
Duty-free stores in Brazil: a study on the regulation and implementation process
Keywords: Lojas francas; Free shop; Duty free; CNPQ::CIENCIAS SOCIAIS APLICADAS